Azotobacter chroococcum Dan Pembenah Tanah Untuk Menurunkan Serapan Kadmium Oleh Tanaman Padi (Oryza sativa L.) - Hindersah, Reginawanti; Nurfitriana, Nofalia; Fitriatin, Betty Natalie (Agrologia, 2017)
Heavy metal contamination in paddy field which came from industry nearby and agricultural input. Increased level of toxic heavy metal cadmium will threat rice production and quality. Bioremediation by used of rhizosphere bacteria is an easy, cheap and effective method to control toxic metal uptake. Pot experiment has been done to study the change in cadmium uptake after biofertilizer Azotobacter chroococcum inoculation and some soil ameliorant. Expirement has been carried out in factorial completely randomized block design with A. chroococcum and ameliorant as treatments.   Either Azotobacter inoculation or soil ameliorant didn’t change soil acidity, the soil still neutral. Rhizosphere of paddy received biochar, hay compost and biochar and inoculated with 108 cfu mL-1 Azotobacter was colonized by more Azotobacter compared to uninoculated one. All plant treated with Azotobacter has higher nitrogen uptake but lower cadmium uptake. This experiment suggested that biofertilizer Azotobacter has a significant role to decrease cadmium uptake by padi, an important food crop.